Aging impairs the essential contributions of non‐glial progenitors to neurorepair in the dorsal telencephalon of the Killifish Nothobranchius furzeri. Issue 9 (24th August 2021) - Van houcke, Jolien; Mariën, Valerie; Zandecki, Caroline; Vanhunsel, Sophie; Moons, Lieve; Ayana, Rajagopal; Seuntjens, Eve; Arckens, Lutgarde
Abstract: The aging central nervous system (CNS) of mammals displays progressive limited regenerative abilities. Recovery after loss of neurons is extremely restricted in the aged brain. Many research models fall short in recapitulating mammalian aging hallmarks or have an impractically long lifespan. We established a traumatic brain injury model in the African turquoise killifish ( Nothobranchius furzeri ), a regeneration‐competent vertebrate that evolved to naturally age extremely fast. Stab‐wound injury of the aged killifish dorsal telencephalon unveils an impaired and incomplete regeneration response when compared to young individuals. In the young adult killifish, brain regeneration is mainly supported by atypical non‐glial progenitors, yet their proliferation capacity clearly declines with age. We identified a high inflammatory response and glial scarring to also underlie the hampered generation of new neurons in aged fish. These primary results will pave the way to unravel the factor age in relation to neurorepair, and to improve therapeutic strategies to restore the injured and/or diseased aged mammalian CNS. Abstract : Neuroregeneration after stab‐wound injury is incomplete in aged killifish, caused by reduced proliferation of specialized non‐glial progenitors (NGPs) and mammalian‐like glial scarring. It seems that aged killifish deploy the restricted regenerative program, typically associated with mammals, instead of successful neurorepair as shown here for young adult killifish.